Serum autofluorescence and biochemical markers in athlete`s response to strength effort in normobaric hypoxia: A preliminary study - Drzazga, Z.; Schisler, I.; Poprzecki, S.; Michnik, A.; Czuba, M. (BioMed Research International, 2019)
human organism has the ability to adapt to hypoxia conditions. Training in hypoxia is used in sport to improve the efficiencyof athletes; however, type of training affects the direction and scope of this process. Therefore, in this study, the usefulness of serumfluorescence spectroscopy to study the assessment of athlete`s response to strength effort in hypoxia is considered in comparisonwith biochemical assay. Six resistance-trained male subjects took part in a research experiment. They performed barbell squats insimulated normobaric hypoxic conditions with deficiency of oxygen 11.3%, 13% 14.3% compared to 21% in normoxic conditions.Fluorescence intensity of tyrosine revealed high sensitivity on strength effort whereas tryptophan was more dependent on highaltitude. Changes in emission in the visible region are associated with altering cell metabolism dependent on high altitude as wellas strength training and endurance training. Significant changes in serum fluorescence intensity with relatively weak modifi-cations in biochemical assay at 3000 m above sea level (ASL) were observed. Training at 5000 m ASL caused changes influorescence parameters towards the normobaric specific values, and pronounced decreases of lactate level and kinase creatineactivity were observed. Such modifications of fluorescence and biochemical assay indicate increased adaptation of the organism toeffort in oxygen-deficient conditions at 5000 m ASL, unlike 3000 m ASL. Fluorescence spectroscopy study of serum accompaniedby biochemical assay can contribute to the understanding of metabolic regulation and the physiological response to hypoxia. The results of serum autofluorescence during various concepts of altitude training may be a useful method to analyze individualresponse to acute and chronic hypoxia. An endogenous tryptophan could be exploited as intrinsic biomarker in autofluorescencestudies. However, these issues require further resear